International Evidence on Government Support and Risk Taking in the Banking Sector - Brandao Marques, Luis (IMF Working Papers; Working Paper ;, 2013)
Government support to banks through the provision of explicit or implicit guarantees affects the willingness of banks to take on risk by reducing market discipline or by increasing charter value. We use an international sample of bank data and government support to banks for the periods 2003-2004 and 2009-2010. We find that more government support is associated with more risk taking by banks, especially during the financial crisis (2009-10). We also find that restricting banks' range of activities ameliorates the moral hazard problem. We conclude that strengthening market discipline in the banking sector is needed to address this moral hazard problem.